2020
DOI: 10.1101/2020.06.03.131888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquilin proteins regulate EGFR levels and activity in lung adenocarcinoma cells

Abstract: 19Ubiquilin proteins (UBQLNs) are involved in diverse cellular processes like ERAD 20 (endoplasmic reticulum associated degradation), autophagy, apoptosis and epithelial to 21 mesenchymal transition. UBQLNs interact with a variety of substrates, including cell 22 surface receptors, transcription factor regulators, proteasomal machinery proteins, and 23 transmembrane proteins. Additionally, previous work from our lab shows that UBQLN1 24 interacts with IGFR family members (IGF1R, IGF2R, INSR) and this interacti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…To further elucidate the biological role of UBQLN1 in breast cancer, the influence of UBQLN1 knockdown on biological behavior in vitro was investigated, in particular regarding metastasis. In contrast to the tumor suppressor role reported in lung cancer cells (6,11,35), the present study found that the knockdown of UBQLN1 inhibited cell migration and invasion, EMT, and MMP2 and MMP9 expression in breast cancer cell lines. EMT has been implicated in carcinogenesis, and confers metastatic properties to cancer cells by enhancing mobility and invasion (37).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…To further elucidate the biological role of UBQLN1 in breast cancer, the influence of UBQLN1 knockdown on biological behavior in vitro was investigated, in particular regarding metastasis. In contrast to the tumor suppressor role reported in lung cancer cells (6,11,35), the present study found that the knockdown of UBQLN1 inhibited cell migration and invasion, EMT, and MMP2 and MMP9 expression in breast cancer cell lines. EMT has been implicated in carcinogenesis, and confers metastatic properties to cancer cells by enhancing mobility and invasion (37).…”
Section: Discussioncontrasting
confidence: 99%
“…While the total number of cases included in the IHC analysis in present study was relatively small, including only 1 case with stage IV, further more well-characterized largescale studies are required to validate the association of UBQLN protein expression with the distant metastasis of breast cancer. UBQLN1 expression has been estimated in several cancer types, including non-small cell lung cancer (NSCLC) (6,11,(34)(35)(36), and breast (20), gastric (12) and ovarian cancer (19). The majority of the findings in the literature cited above are consistent with the findings of the present study, suggesting that UBQLN1 promotes cancer progression and may play an oncogenic role in cancer.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations